Long-term regenerative practices enhance in-field biodiversity and soil health for sustainable crop yields - Hawes, Cathy; Christie, Andrew; Banks, Gillian; Boldrin, David; Brandt, Jacqueline; Iannetta, Pietro; Swyst, Isabella; Turner, Izzy (Frontiers in Sustainable Food Systems, 2025)
Agricultural intensification has resulted in arable systems dominated by monocultures that are reliant on agrochemical inputs and frequent tillage to maintain high crop yields. This has caused significant decline in farmland biodiversity and soil health, further increasing the need for chemical inputs to regulate system processes. Regenerative practices aim to reverse this trend and capitalise on biodiversity-driven ecosystem functions that determine the long-term sustainability of agricultural production. However, despite a general acceptance of the potential benefits of this approach, there is currently very little supporting evidence from long-term, field scale experimental data. A whole-systems and nature-based approach for designing and implementing a regenerative cropping system at the Hutton’s Centre for Sustainable Cropping long-term platform has demonstrated the practical application of theoretical, outcomes- and biodiversity-based frameworks in a commercially realistic setting. Best practice management options were combined in a cropping system that, rather than conserving soil and biodiversity at the expense of crop production, aimed to maintain yields with less reliance on agrochemical inputs by simultaneously promoting soil health, crop fitness and biodiversity. Soil physical properties and biological processes were enhanced, plant diversity and the abundance of beneficial plant and invertebrate species were increased, and crop yield was maintained at levels comparable to the national average. A barrier to uptake of low input, regenerative practices is the perception of risk. Data-driven evidence for the positive and negative impacts of regenerative approaches on crop production and the environment is needed for farmers to make informed management decisions. Particularly important is an understanding of the balance between short-term costs and longer-term benefits as the system gradually stabilises and starts to deliver increased resilience to future environmental perturbation. This highlights the need for long-term, whole-system and field-scale studies to provide commercially realistic predictions of risks, costs and benefits for growers wishing to adopt regenerative cropping practices.